THEORETICAL APPROACHES TO CRISIS MANAGEMENT IN SECURITY ENTERPRISES UNDER ECONOMIC INSTABILITY - FEDCHENKO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article provides a comprehensive analysis of crisis management in the security services sector, focusing on the specificities of the security service market, crisis risks, and effective management tools to maintain stability in times of economic instability. It identifies the competitive nature of the market, dependence on client trust, and significant costs related to personnel and security technologies. Several crisis factors are discussed, including decreased demand due to economic downturns, growing security threats due to social and political factors, and operational readiness challenges. Crisis management tools are explored, such as business restructuring, innovation implementation like automated monitoring systems, and active human resource management. Economic, political, and social factors are examined to highlight the need for quick adaptation to changing conditions. Regular strategy analysis and monitoring are recommended to improve operational efficiency during crises. It has been proven that funding constraints can hinder investment in the upgrade of technical resources, which negatively affects the quality of services provided. It has been established that a reduction in budget allocations may lead to staff cuts or wage reductions, which impacts personnel efficiency. It has also been established that new regulations or changes in legislation may require businesses to quickly adapt to new safety standards, non-compliance with which threatens fines or even business closure, thereby increasing risks for companies in conditions of economic uncertainty. The importance of financial cost-saving measures and attracting investments is emphasized. The role of innovations, including AI technologies for monitoring and security system upgrades, is underlined to enhance competitiveness. Effective communication with clients is identified as crucial to maintaining trust during economic challenges. A framework is presented, considering economic instability factors, providing recommendations to improve crisis management effectiveness in security companies. The combination of systemic, strategic, and adaptive approaches is concluded as essential to ensuring the resilience and efficiency of businesses during periods of economic uncertainty.
Keywords: сrisis management; еconomic instability; security services; enterprise; risks; technological upgrades; financing